Contours of death and disease in early modern England - Dobson, Mary J. (Cambridge studies in population, economy and society in past time, 1997)
Using a wide range of sources for the south-east of England, Dobson highlights the tremendous variation in levels of mortality across geographical contours and across two centuries, exploring the causes and consequences of these variations.